READINESS MASTERS OF SOCIAL WORK TO PROFFESSIONAL MOBILITY: CONCEPTUAL AND CATEGORY ANALYSIS - Ekaterina Klushina (Вестник Северо-Кавказского федерального университета)
This article discusses the essential and conceptual characteristics of the phenomenon of professional mobility. The article analyzes the category of«readiness», and revealed a functional and personal-activity approach to this phenomenon. The article describes the structure and content of components of readiness to professional mobility: motivational-value, intellectual-cognitive, operate-practical, emotionally-volitional. In the article offered the author's interpretation of the concept of «readiness to professional mobility master of social work».